2009
DOI: 10.1152/ajprenal.00181.2009
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive guide to the ROMK potassium channel: form and function in health and disease

Abstract: The discovery of the renal outer medullary K+ channel (ROMK, K(ir)1.1), the founding member of the inward-rectifying K+ channel (K(ir)) family, by Ho and Hebert in 1993 revolutionized our understanding of potassium channel biology and renal potassium handling. Because of the central role that ROMK plays in the regulation of salt and potassium homeostasis, considerable efforts have been invested in understanding the underlying molecular mechanisms. Here we provide a comprehensive guide to ROMK, spanning from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
144
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 179 publications
1
144
0
2
Order By: Relevance
“…Mg 21 binds to ROMK at a specific location on its cytoplasmic surface (78)(79)(80). By binding to ROMK at this site, Mg 21 blocks the channel's pore from the inside and prevents K 1 from being secreted.…”
Section: Regulation Of Distal Tubule Potassium Transportmentioning
confidence: 99%
“…Mg 21 binds to ROMK at a specific location on its cytoplasmic surface (78)(79)(80). By binding to ROMK at this site, Mg 21 blocks the channel's pore from the inside and prevents K 1 from being secreted.…”
Section: Regulation Of Distal Tubule Potassium Transportmentioning
confidence: 99%
“…43 They are present in many cell types where they play an important role in regulation or maintenance of the cell membrane potential, such as neurons, 44 Alternative splicing generates three different ROMK isoforms (ROMK1-3) with differential expression along the nephron: ROMK2 mediates apical K þ recycling in the TAL, whilst ROMK1 and ROMK3 in the distal nephron mediate K þ secretion. 45 Regulation of ROMK activity occurs by modulating the number of channels present at the cell surface, or the activity of membrane-resident channels.…”
Section: Bartter Syndromementioning
confidence: 99%
“…[1][2][3] Therefore, ROMK inhibition could be potassium sparing while causing natriuresis/diuresis, which is a favorable feature for a novel diuretic and would differentiate ROMKi from conventional loop diuretics such as furosemide that cause hypokalemia. 19,20 Indeed, in our present studies, ROMKi B did not cause increased urinary K + excretion and had no effect on plasma K + concentration.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Thus, ROMK plays a critical role in the regulation of renal sodium reabsorption and the body's potassium homeostasis. Human genetic studies indicated that loss-of-function mutations in ROMK cause type II Bartter syndrome, [4][5][6] featuring polyuria, polydipsia, salt wasting, hypokalemia, alkalosis, hypercalciuria, low blood pressures, elevated plasma renin and aldosterone, and excess production of renal prostaglandins.…”
mentioning
confidence: 99%